Motor neuron-derived induced pluripotent stem cells as a drug screening platform for amyotrophic lateral sclerosis - Amorós, Mariana A.; Choi, Esther S.; Cofré, Axel R.; Dokholyan, Nikolay V.; Duzzioni, Marcelo (Frontiers in Cell and Developmental Biology, 2022)
The development of cell culture models that recapitulate the etiology and features of nervous system diseases is central to discovering new drugs and their translation onto therapies. Neuronal tissues are inaccessible due to skeletal constraints and the invasiveness of the procedure to obtain them. Thus, the emergence of induced pluripotent stem cell (iPSC) technology offers the opportunity to model different neuronal pathologies. Our focus centers on iPSCs derived from amyotrophic lateral sclerosis (ALS) patients, whose pathology remains in urgent need of new drugs and treatment. In this sense, we aim to revise the process to obtain motor neurons derived iPSCs (iPSCs-MN) from patients with ALS as a drug screening model, review current 3D-models and offer a perspective on bioinformatics as a powerful tool that can aid in the progress of finding new pharmacological treatments.